2021
DOI: 10.3390/biomedicines9101447
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System in Duchenne Muscular Dystrophy Pathogenesis

Abstract: Growing evidence demonstrates the crosstalk between the immune system and the skeletal muscle in inflammatory muscle diseases and dystrophic conditions such as Duchenne Muscular Dystrophy (DMD), as well as during normal muscle regeneration. The rising of inflammation and the consequent activation of the immune system are hallmarks of DMD: several efforts identified the immune cells that invade skeletal muscle as CD4+ and CD8+ T cells, Tregs, macrophages, eosinophils and natural killer T cells. The severity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 112 publications
1
22
0
Order By: Relevance
“…The levels of infiltration for active B cells, CD56dim natural killer cells and type 17 T helper cells were decreased in DMD. These differences might be associated with DMD occurrence and progression, which were in good agreement with those from previous studies (Tripodi et al, 2021) and further confirmed the importance of the immune response in the pathogenesis of DMD. It is generally known that macrophages are an essential component of human innate immunity, and these cells can also exert potential influence on the pathogenesis of DMD.…”
Section: Discussionsupporting
confidence: 92%
“…The levels of infiltration for active B cells, CD56dim natural killer cells and type 17 T helper cells were decreased in DMD. These differences might be associated with DMD occurrence and progression, which were in good agreement with those from previous studies (Tripodi et al, 2021) and further confirmed the importance of the immune response in the pathogenesis of DMD. It is generally known that macrophages are an essential component of human innate immunity, and these cells can also exert potential influence on the pathogenesis of DMD.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, IL-6 mRNA was attenuated with Smad8 silencing. IL-6 is a pro-inflammatory cytokine that exacerbates the dystrophic process by promoting the recruitment of neutrophils and other immune cells to sustain an inflammatory milieu [ 52 , 53 ]. This impedes muscle regeneration and promotes fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It includes destruction of muscle fiber membrane, imbalance of calcium balance, muscle necrosis and exhaustion, accompanied by adipose tissue proliferation and immune cell infiltration ( 28 , 29 ). Moreover, growing evidence demonstrates the crosstalk between the immune system and the skeletal muscle in inflammatory muscle diseases, including DMD ( 15 , 30 , 31 ). However, these downstream pathways cannot elucidate the pathogenesis of DMD alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, weighted gene coexpression network analysis (WGCNA) can describe the connections among various genes by constructing a co–expression network and identify phenotype-related modules, which is more effective to investigate the key pathways and genes in many human disorders ( 13 , 14 ). In addition, most immune system components are demonstrated in the initiation and progression of DMD ( 15 ). Therefore, our goal was to perform a detailed analysis of molecular mechanisms, diagnostic and therapeutic targets underlying DMD with the transcriptome, proteome, and immune-related features.…”
Section: Introductionmentioning
confidence: 99%